Afetividade e cognição no uso de redes sociais digitais por idosos - De Marchi, Barbara Frigini (2019)
We live in a society networked through the internet, which is simultaneously an increasingly aging society. Together, these factors contribute to causing the number of elderly users of digital social networks (DSN) to increase significantly. Thus, this dissertation proposes to investigate affective and cognitive aspects involved in the use of these networks by older audiences. We interviewed 26 people, who were homogeneously divided into sex; were aged between 65 and 74 years old; had finished at least elementary education; had smartphones or computers; and also had access to DSNs. The sample was given for convenience, based on the snowball method. Data were collected through individual interviews, based on two semistructured scripts, which were in turn guided by the Piagetian clinical method. Data analysis was based on content analysis, prioritizing the qualitative reading. The results indicated that the elderly, even though not belonging to a native generation of these technologies, are active and participative in several DSNs, which shows that they are concerned about keeping up with technological evolutions and, therefore, feel that they belong to the current social context. WhatsApp appeared prominently among the DSNs mentioned, being both the most used and preferred. Regarding the actions they perform, respondents listed exchanging text messages and multimedia files; reading news; working; and wishing happy birthday. We verified that the element that motivates them the most to access DSNs is communication, and that digital network use can favor social and affective relations, contributing to a more positive aging. Participants also showed that they have made new affective bonds and diminished the feeling of loneliness through these networks, broadening their relationships and interpersonal communication. This study, therefore, provided an understanding that the use of DSNs can potentially mobilize affective and cognitive aspects among the elderly, and promote development as networks act as a source of imbalances, unlike the old paradigms of Psychology, which saw old age solely as a period of losses. We hope that this study will contribute to other investigations focusing on old age and new technologies from the perspective of Developmental Psychology. We also hope that the data can serve as a subsidy for future academic productions, as well as for public policies.